Role of Interleukin 33 During Infection with Toxoplasmosis in Rheumatoid Arthritis Patients - Israa Kasim Al-Aubaidi1, Marwa Ali Al- Oqaily1, Sadia Shahab Hamad2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Toxoplasma gondii is avery common obligate intercellular parasite with highest infection rate among worlds populations. The Rheumatoid arthritis (RA) considered as an autoimmune disease characterized by loss immunological tolerance to self-antigens. Present study Aims to detection the seroprevalence of toxoplasmosis among RA patients and healthy control and evaluate concentrations of IL-33 to understand their role during infection. Seropositive cases of IgG was 36.7% percentage in RA patients with highest value of IgG 0.395 IU/ml while control group was 100% seronegative. Three cases only were seropositive to IgM with 1.17% and their mean 0.54 IU/ml.IL-33 levels in RA patients with toxoplasmosis was highest 187.74± 33.24 pg/ml when compared with RA patients 107.88±18.41 pg/ml and control group 55.59±25.75 pg/ml ,there was a significant differences in comparison between studied groups.